(untitled) (International journal of artificial intelligence, 2025)
Improving the intellectual culture of future teachers through philosophy education is very different from teaching other subjects. This difference comes from the fact that philosophy is a branch of spiritual culture. In this article, opinions on the importance of teaching philosophy in the development of the intellectual culture of future teachers, in the development of the ability to analyze any information freely, freely and independently in the context of globalization, are presented.